Wen zhang zuo fa - Xia, Mianzun, 1886-1946 (Pre-Kangzhan and Kangzhan Period Preservation Project, 1941)
Fen hsü yen, tso che ying yu ti tʻai tu, chi hsü wen, shuo ming wen, i lun wen, hsiao pʻin wen 6 chang.